2017
DOI: 10.1097/md.0000000000008602
|View full text |Cite
|
Sign up to set email alerts
|

Chorea associated with nonketotic hyperglycemia

Abstract: Introduction:This is a unique case of nonketotic hyperglycemic (NKH) chorea in 84-year-old Asian woman. The patient had a history of type 2 diabetes mellitus more than 30 years, but had a poor control of blood sugar. She complained of acute onset of bilateral limb involuntary activities, and being easy to fall within a week. Laboratory testing disclosed hyperglycemia (669 mg/dL), glycated hemoglobin (14%), and normal ketones. The brain computed tomography scan and magnetic resonance imaging did not disclose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 12 publications
3
22
1
9
Order By: Relevance
“…One case showed leukoaraiosis and multiple cortical ischemia, but no hyperintensisty in putamen [9]. A recent study reported that a DC patient with nonketoic hyperglycemia did not show any abnormalities in the brain MRI and computed tomography (CT) [10]. In our case, patient 2 did not show typical DC symptoms, such as high intensity area in basal ganglia in the brain MRI.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…One case showed leukoaraiosis and multiple cortical ischemia, but no hyperintensisty in putamen [9]. A recent study reported that a DC patient with nonketoic hyperglycemia did not show any abnormalities in the brain MRI and computed tomography (CT) [10]. In our case, patient 2 did not show typical DC symptoms, such as high intensity area in basal ganglia in the brain MRI.…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, the lack of evidence for atherosclerotic lesions in the carotid artery ultrasonography and the brain magnetic resonance angiography added to a lack of arrhythmias support the notion that these multiple small hyperintensities did not represent atherosclerotic lesions in our patient 2. Chang et al proposed two types of DC: a common type showing hyperglycemia, choreic movement with typical radiographic imaging in brain MRI or CT and uncommon type showing chorea with negative imaging changes [10]. Patient 2 exhibited uncommon type of DC.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic radiographic manifestations of non-ketotic hyperglycemia-related hemichorea-hemiballism are high-density changes in brain CT, high signal changes in brain MRI T1-weighted sequences, and equal or low signal in MRI T2-weighted sequences of the contralateral striatum. [1417] Clinicians may interpret the initial high-density lesion of brain CT as acute hemorrhage. The hyperglycemic state promotes deposition of a T1-intense mineral, such as calcium or manganese, which recovers after glucose is normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai kondisi seperti penyakit neurodegeneratif, serebrovaskular, imunologi, neoplastik, infeksi, dan kelainan metabolik dikenal sebagai penyebab sekunder dari HCHB. 4 Ingle dan Gupta tahun 2016 melaporkan bahwa stroke iskemik akut biasanya ditandai dengan gejala seperti paresis/paralisis anggota gerak atau kebas. Adapun gejala yang jarang terjadi pada stroke iskemik akut adalah gangguan gerak hiperkinetik seperti HCHB, mioklonus, tics, dan tremor rubral.…”
Section: Pendahuluanunclassified